PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT DURAQUIPT CEMERLANG LIMO DEPOK - Muhammad Bintang Nugraha; Widia Astuti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study was to determine the effect of physical work environment and work discipline on employee performance at PT Duraquipt Cemerlang Limo Depok both partially and simultaneously. The research method used is quantitative with a population of 283 people. Using the Slovin sample technique, a sample of 74 people was obtained. The analysis method in data management is by validity test, reliability test, classical assumption test, linear regression test, correlation coefficient test, determination coefficient test, and hypothesis test. The results showed that there was an influence of leadership on employee performance indicated by the t count value (8.045)> t table (1.666) and a significance value (0.000 <0.05) in the determination coefficient test of 0.473 or 47.3% correlation coefficient of 0.688 where the work environment on employee performance has a strong level of relationship strength. There is an influence of work discipline on employee performance indicated by the calculated t value (12.262) > t table (1.666) and a significance value (0.000 <0.05) in the determination coefficient test of 0.676 or 67.6% correlation coefficient of 0.822 where work discipline on employee performance has a strong level of relationship strength. And there is an influence of the work environment and work discipline on employee performance indicated by the results of the simultaneous f test obtained f count (77.165) > f table of (3.126) with a significance value (0.000<0.05) in multiple linear regression Y = 4.212 + 0.150 X1 + 0.750 X2, The correlation coefficient is 0.828, where the physical work environment and work discipline on employee performance have a strong level of relationship strength.